Electronic performance assessment : applying microsoft business scorecards accelerator in a small public sector serving organisation - Rabie, Jaco (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Public and Development Management))--University of Stellenbosch, 2006.